Relationship between Vaginal Sialidase Levels with Threatened of Preterm Labour - Bambang Sulistyo; Najoan N Warouw; Eddy Suparman (Indonesian Socety of Obstetrics and Gynecology, 2018)
Objective: To investigate the association between vaginalsialidase levels and threatened of preterm labor.Methods: A cross sectional study design was used. Subjects weredivided into two groups; the first group were pregnant women withthreatened of preterm labour, whereas the second were pretermpregnant women in Prof. Dr. R.D. Kandou Manado hospitals andnetwork hospitals, during the period between August 2016 andOctober 2016. Data were analyzed with SPSS version 20 to see thesignificancy levels.Results: From the 16 pregnant women with threatened ofpreterm labor and 16 pregnant women with preterm pregnant,the statistical t test showed that there were significant differencesaverage level of sialidase vagina between the threatened ofpreterm labor and preterm pregnant group (p = 0.000).Conclusion: There is a relationship between the incidencethreatened of preterm labor with vaginal sialidase levels.Keywords: bacteria, threat of preterm labour, vaginal sialidase